PENGEMBANGAN LKS BAHASA JERMAN BERBASIS PENDEKATAN SAINTIFIK UNTUK SISWA SMA - Shinta Saputri Tjindera, May (LATERNE, 2017)
Learning German, there are four skills to be mastered including listening, speaking, reading, and writing. To enhance students’ skills teacher can use learning sheet as the alternative. Azhar (1993: 78) stated that having learning sheet, there is no need for the students to write a summary as the learning sheet is the summary itself. Learning sheet may ease the students master the whole material given. Those are the basics of developing a learning sheet based on the scientific approach for students of senior high school. The research question under this study is “How is the result of developing scientific approach based learning sheet to learn Germany especially Familie for XI graders in odd semester” The aim of this study is developing scientific approach based learning sheet to learn Germany especially Familie for XI graders in odd semester as well as knowing the quality of the learning sheet. This study belong to R&D (Research & Development) method. The data collected were from books of Studio D A2, Kontakte Deutsch 2, Deutsch ist einfach, and a website of Deutsch Schule. Those data were further analysed by using three stages of selecting the data, classifying the data, and arranging the data. The learning sheet has been composed of 30 pages divided into 2 lectures.   Keywords: developing learning sheet, scientific approach